O salto transmidiático dos super-heróis: HQ - Filme - Game - Costa, Thiago Sanches (2012)
This research investigates the existent relations between digital transposition phenomenon and transmedia on a mutual influence context of comic book and game culture and its repercussions on digital storytelling structures. The methodological proposal is to read and deepen the relations between different concepts in search of its understanding process as a digital culture phenomenon, identifying as an historical action previous to transmedia storytelling: the transmediatic jump. For this, it uses superheroes, characters born in comic books at the beginning of the twentieth century, to show this path and the passage from the concept of transformation by the transmediatic jump to the transposition phenomenon and the transmedia object. It also show that the model object has philosophical, psychological, cultural and ontological features that made them leading figures on the modern entertainment industry that only exists on transmedia plurality. The research done is theoretical, as it s a study that looks forward to concept rebuilding and to enhance theoretical fundaments. The utilized method is bibliographic research, using prevailing materials about the theme, such as: Scott McCloud and Will Eisner as the main references about comic books structure and language; Gerard Jones research as the most used source about superheroes and its creators History; Joseph Campbell points the mythological way and Richard Reynolds connect it to superhero, central to comprehend storytelling that flows from a media support to other; and Janet Murray is the perfect complement to understand how this structures works at the digital game environment. This is how the superheroes transmedia jump, comics-movie-game, discussion base is formed